Object feature extraction method, object feature inspection method and object feature extraction system - LIN ZIQIAO; CHEN JIANXIN; LUO ENNI (2023)
A system and method for extracting or inspecting features of an object using thermal imaging, and a method of inspecting an apparel product object. The system includes a heat influence source configured to heat or cool a subject; an imager arranged to capture a plurality of images of the subject when the subject is subjected to the thermal effect; and an image processor arranged to process the plurality of images and to distinguish a feature of interest from other portions of the object presented on the plurality of images. 一种使用热成像来提取或检查对象的特征的系统和方法，以及一种检查服装产品对象的方法。所述系统包括热影响源，其被设置为加热或冷却对象；成像器，其被设置为当所述对象经受所述热影响时捕获所述对象的多个图像；以及图像处理器，其被设置为处理所述多个图像并将感兴趣特征与呈现在所述多个图像上的所述对象的其他部分区分开。